Moderation Internal Control System: PSAK Adoption IFRS and Dysfunctional Audit Behaviour on Audit Quality - Ratna Mappanyuki; S Sumiyati; N Nengsih; Syamsu Alam (Universitas Pendidikan Indonesia, 2023)
This study aims to empirically illustrate the influence of PSAK adoption IFRS, with its interaction with dysfunctional audit Beha-vior, on audit quality, utilizing the internal control system as the moderation variable. The data collection comes from Indonesia’s state-owned enterprises (SOE) employees located in Jakarta with criteria gender, level of education, age, and length of service. The survey on questionnaires and the analysis were executed through the Smart PLS 3.0. The pivotal discovery reveals a noteworthy impact of IFRS Adoption on audit quality. These findings align cohesively with agency theory, suggesting that interactions with-in agency relationships frequently give rise to knowledge inequ-ality, manifesting as information asymmetry. Highlighting the im-perative of transparency, it is emphasized that financial reports crafted with transparency possess the potential to shape the quality of resultant financial statements. Intriguingly, this study concludes with the unexpected revelation that there is no moderation (predictor moderation) of the internal control system on the influence of applying IFRS Adoption on audit quality. This underscores the assertion that situational leadership attains greater efficacy when supported by conducive leadership tailored to specific circumstances. Regarding theoretical and practical im-plications, no direct interaction is discerned between the internal control system, IFRS Adoption, and Dysfunction Audit Behavior. The moderator test findings in this study serve as moderation predictors and unveil how the internal control system variable functions solely as a predictor in the established research model, thereby contri-buting novelty to the existing literature.